The study on Ibn Khaldun: Big Data visualization and knowledge graph analysis - Ren, Huichan; Abdullah, Suhaila (Bibliotecas. Anales de investigación, 2024)
Objective: This study employs bibliometric approaches to systematically analyze the structural research development of Ibn Khaldun. Design/Methodology/Approach: A total of 195 publications from the Web of Science database, published between 2014 and 2023, were selected and thoroughly investigated using visual analysis tools, including VOSviewer and Scimago Graphica. Results/Discussion: The main finding reveals the study of Ibn Khaldun faces obstacles to growth and requires the immediate exploration of new research channels. Furthermore, the main topics of research on Ibn Khaldun are comparisons with Western and Arabic thinkers and analyses of his perspectives on sociology, history, and politics. Conclusion: Ibn Khaldun is a significant scholar from the medieval Arab era. His ideas continue to offer tremendous inspiration for modern civilization. There is still a substantial amount of unexplored terrain when it comes to investigating Ibn Khaldun’s research methods, contents, and directions. Originality/Value: The primary objective is to provide valuable insights for future Ibn Khaldun research by offering a detailed understanding of the prevailing research landscape.